Implementation of Gamification Through The Curipod Platform in Fortering Critical Thinking Skills in Islamic Religious and Character Education at SMA Negeri 1 Bumiayu - Hilda Rahmawati Fitri; Shobrun Jamil (Education Reserach Center, 2026)
This study aims to describe the implementation of gamification through the Curipod platform in fostering students’ critical thinking skills in Islamic Religious Education and Character Education for Grade XI senior high school students. The study is motivated by conventional learning practices that limit dialogue and reflection, despite the Merdeka Curriculum’s emphasis on critical reasoning aligned with 21st-century learning. Therefore, Curipod is considered a relevant interactive digital learning alternative to support critical thinking development. This study employed a qualitative descriptive approach involving one teacher of Islamic Religious Education and Character Education and Grade XI students at SMA Negeri 1 Bumiayu. Data were collected through classroom observations, semi-structured interviews, and learning documentation. Data analysis followed the stages of data reduction, data display, and conclusion drawing, with data trustworthiness ensured through triangulation. The findings indicate that the implementation of gamification through the Curipod platform can be well integrated into Islamic Religious Education and Character Education learning and aligns with the objectives of the Merdeka Curriculum. Curipod facilitated content delivery, discussion, and reflection, shifting learning from teacher-centered to student-centered practices. This encouraged students to actively express opinions, provide reasoning, and critically reflect on Islamic values in a more contextual manner.